CNS Targets of Adipokines. Issue 4 (12th September 2017) - Beall, Craig; Hanna, Lydia; Ellacott, Kate L. J.
ABSTRACT: Our understanding of adipose tissue as an endocrine organ has been transformed over the last 20 years. During this time, a number of adipocyte‐derived factors or adipokines have been identified. This article will review evidence for how adipokines acting via the central nervous system (CNS) regulate normal physiology and disease pathology. The reported CNS‐mediated effects of adipokines are varied and include the regulation of energy homeostasis, autonomic nervous system activity, the reproductive axis, neurodevelopment, cardiovascular function, and cognition. Due to the wealth of information available and the diversity of their known functions, the archetypal adipokines leptin and adiponectin will be focused on extensively. Other adipokines with established CNS actions will also be discussed. Due to the difficulties associated with studying CNS function on a molecular level in humans, the majority of our knowledge, and as such the studies described in this paper, comes from work in experimental animal models; however, where possible the relevant data from human studies are also highlighted. © 2017 American Physiological Society. Compr Physiol 7:1359‐1406, 2017.